Impact of foreign direct investment in services on service trade in Asean countries - Khamis, Khamis Msellem (2013)
Since 1990s there has been tremendous increase in the movement of FDI especially to developing and emerging markets due to the rapid liberalization policies initiated by these countries. The issue of FDI continues to attract the interest of scholars and policymakers due to its anticipated spillover effects on economic growth and development of the host countries. Intense competition among emerging economies and developing countries to entice foreign capital has led to formulation of various measures as FDI stands as the most important foreign financing in these countries. There are two main objectives of the study. First objective explores the determinants of services FDI, while the second objective examine the the impact of services FDI on services trade. There exist two conflicting arguments in respect to FDI-trade relationship. The first argues for a positive relationship meanwhile the second holds that FDI and trade are negatively related. The stated objectives were achieved using static linear panel data analysis namely; pooled OLS, random effects and fixed effects models covering data from 2000 until 2010. As for the first objective, the finding shows that market size, trade openness, human capital and the availability of quality infrastructure are important determinants of services FDI inflow for the ASEAN countries. In addition, the study finds insignificant relationship between services FDI and services trade.Therefore, it is crucial for the ASEAN countries to invest substantially in the education sector in order to produce a quality and highly skilled workforce that are required in the services subsectors. In addition, the government and central bank should play a key role in formulating appropriate monetary, fiscal and trade policy to effectively control the rising inflation rate if they are bale to identify the main causes of such inflation. Furthermore, well-developed, reliable and quality communications infrastructure will reduce costs and increase efficiency for investors, and hence, will convince them to choose ASEAN countries, in particular, as their investment destination. The ASEAN region has to extend their ICT networks in almost all provinces or states within respective countries along with reduction of internet, mobile and telephone subscription costs.